The ROKS Nomogram for Predicting a Second Symptomatic Stone Episode - Rule, Andrew D. (J Am Soc Nephrol, 2014)
Most patients with first-time kidney stones undergo limited evaluations, and few receive preventive therapy. A prediction tool for the risk of a second kidney stone episode is needed to optimize treatment strategies. We identified adult first-time symptomatic stone formers residing in Olmsted County, Minnesota, from 1984 to 2003 and manually reviewed their linked comprehensive medical records through the Rochester Epidemiology Project. Clinical characteristics in the medical record before or up to 90 days after the first stone episode were evaluated as predictors for symptomatic recurrence. A nomogram was developed from a multivariable model based on these characteristics. There were 2239 first-time adult kidney stone formers with evidence of a passed, obstructing, or infected stone causing pain or gross hematuria. Symptomatic recurrence occurred in 707 of these stone formers through 2012 (recurrence rates at 2, 5, 10, and 15 years were 11%, 20%, 31%, and 39%, respectively). A parsimonious model had the following risk factors for recurrence: younger age, male sex, white race, family history of stones, prior asymptomatic stone on imaging, prior suspected stone episode, gross hematuria, nonobstructing (asymptomatic) stone on imaging, symptomatic renal pelvic or lower-pole stone on imaging, no ureterovesicular junction stone on imaging, and uric acid stone composition. Ten-year recurrence rates varied from 12% to 56% between the first and fifth quintiles of nomogram score. The Recurrence of Kidney Stone nomogram identifies kidney stone formers at greatest risk for a second symptomatic episode. Such individuals may benefit from medical intervention and be good candidates for prevention trials.